The Influence of Standard Understanding of Government Accounting, Experience and Use Of Technology on The Performance of BPK Inspectors Representative of Riau Province During The Covid-19 Pandemic - Ariyanto, Sanusi (Universitas Pamulang, 2022)
This research aimed to find out the influence of Standard Understanding of Government Accounting, Experience, and Technology as independent variables on the performance of Examiner as dependent variable at BPK Office, Riau Province. Descriptive method was used to find out this influence in the form of correlational study with quantitative approach. It was expected to obtain more accurate measurement result about the response given by respondents until the data in the form of numbers could be processed by using staticstics namely validity test, reliability test, and T and F hypothesis test. The population in this research were limited on the finance examiner (Auditor) of BPK Riau Province. The research sample used in this research were 30 respondents. The sample selection used questionnaire with liker scale. The data analysis was conducted at significant level 95%. The analysis instrument used in this research was regression analysis. The analysis result found out that the standard understanding of Government Accounting and Technology had positive influence on the performance while experience did not have influence on performance based on T-test. From F test, it was found that understanding of SAP, experience, and technology simultaneously and positively influence the performance of BPK Riau Province during the pandemic.